The recognition of DNA cleavage sites by porcine spleen topoisomerase II. - Huang, H W (1992)
The cutting sites specificity of topoisomerase II from porcine spleen were determined by a modified Sanger's DNA sequencing method. The topoisomerase II prefers to cut DNA at the 3' side of A and leave 5' protruding end with two staggering bases. Through the free energy analysis for DNA duplex, we also found that the topoisomerase II seemed cut DNA preferably at energetically unstable regions. So it is concluded that the specific DNA cutting by porcine spleen topoisomerase II has two structural recognition factors: one is to localize around the energetically unstable region and another is to act at the 3' side of A base.